Insight Into Non-Pathogenic Th17 Cells in Autoimmune Diseases - Wu, Xinyu; Tian, Jie; Wang, Shengjun (Frontiers in Immunology, 2018)
Th17 cells are generally considered to be positive regulators of immune responses because they produce pro-inflammatory cytokines, including IL-17A, IL-17F and IL-22. Cytokine production not only promotes accumulation of immune cells, such as macrophages, neutrophils and lymphocytes, at inflammatory sites but can also cause tissue pathologies. Conversely, certain Th17 cells can also negatively regulate immune responses by secreting immunosuppressive factors, such as IL-10; these cells are termed non-pathogenic Th17 cells. In this review, we summarize recent advances in the development and regulatory functions of non-pathogenic Th17 cells in autoimmune diseases.